Phytochemical and Biological Investigations of Crude Extracts of Astragalus pisidicus - Esra Aydemir; Elif Odabaş Köse; Serap Özkaya Gül; Alaaddin Korkut; A. Cansu Kilit; Mehmet Engin Celep; Mustafa Yavuz; R. Süleyman Göktürk; Cengiz Sarikurkcu (Pharmaceuticals)
Background/Objectives: Astragalus L. is a genus of the Fabaceae family, encompassing over 3000 species globally, with 380 species found in Turkey. This is the inaugural examination of the phytochemical, antioxidant, antibacterial, and cytotoxic properties of Astragalus pisidicus. Methods: The water and methanolic fractions of four parts (stems, flowers, leaves, root) as well as the whole plant were quantified and identified by Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometry (LC–ESI–MS/MS) analysis. Cell death was assessed using the WST-1 assay, while apoptosis was identified by colorimetric protease assay for caspase 2, -3, -6, -8, and -9, as well as cellular DNA fragmentation assay. Antioxidant activity of A. pisidicus water and methanolic extracts was investigated with eight different assays. Antimicrobial activities of the extracts were evaluated against 16 bacterial strains by disc diffusion and broth microdilution methods. Results: A total of 13 phytochemicals were detected in the extracts at various concentrations. Hesperidin (147–40,174 µg/g extract) and hyperoside (363–2677 µg/g extract) comprised the principal constituents among the extracts. Fm (IC50 = 9.57 µg/mL), Rm (IC50 = 14.89 µg/mL), and Sm (IC50 = 9.57 µg/mL) were evaluated as active crude extracts on H1299, HT-29, and Panc-1 cells, while Rm (IC50 = 32.057 µg/mL) and Fm (IC50 = 64.25 µg/mL) were assessed as moderately active on MCF-7 and 22RV1 cells, respectively. The elevation of caspase 2, 3, 6, 8, and 9 enzyme activities, along with DNA fragmentation, signifies that the mode of cell death is apoptosis. According to the disc diffusion test results, Fm, Lm, Sm, and WPm extracts exhibited antimicrobial activity against gram (+) bacteria. Conclusions: A. pisidicus elicited apoptotic cell death in cancer cells selectively by the activation of caspases and subsequent DNA fragmentation and may serve as a novel source of an apoptosis-inducing anticancer drug.